Improving the method of rotational broaching in the production of profile openings on the lathes of turning group - Vasilyev, Anatoly; Popov, Stanislav; Vasilyev, Eugene; Pavelieva, Anna (Eastern-European Journal of Enterprise Technologies, 2017)
We examined methods of manufacturing profile openings on the metal-cutting machines by the rotational broaching method. Based on the generalized results of analysis of the methods for manufacturing profile openings, we proposed a method of rotational broaching. Bits for drilling machines or screwdrivers are used as the tool. Hardness of the bit is quite high; therefore, making a centering opening in it is difficult. The problem is solved by pressing a transition bushing onto the bit, with a centering opening made in advance. Implementation of the method requires a Morse cone with a welded plate. This allows fixing the rotating centre in a tool carrier. The proposed method makes it possible at minimal financial cost to perform the shaping of profile openings within a wide range of both the shape and nominal dimensions. The method is based on the effect of self-centering and, therefore, does not require preliminary adjustment. Adjusting tool entrance angle is achieved by displacing a transverse support of the lathe and by tool carrier rotation. In addition, in the production of profile opening, its input cone is formed, which provides for easy installation of the wrench to transmit rotational moment without losing load capacity. The studies conducted defined suboptimal values of the input variables that are accepted as rational in the examined technological process of rotational broaching. These are: a tool entrance angle (1.5...2.5 degrees), its supply (0.1...0.3 mm/rev) and the rate of processing (15...25 m/min)